The effects of affect. A plea for distance between the human and non-human. Issue 2 (4th May 2018) - de Block, Greet; Vicenzotti, Vera
Abstract: Agreeing with Elizabeth Meyer to put aesthetics back on the landscape agenda, this article takes issue with the recent turn to the theoretical discourse of affect that advocates a continuity between object and subject, between the human and non-human. In this article we focus on the effects of the notion of affect in ecological landscape design and argue for an environmental aesthetics that sustains distance by discussing the concepts of 'disinterestedness' and the sublime. An aesthetics sustaining distance between subject and object could offer ways to 'free' the beholder and create space to reflect actively and critically on the connection between the human and non-human. As much an attempt to inject the political as an attempt to question organicist tendencies in landscape theory and design, this article focuses on the effects of affect, foregrounding the risks of shuffling human/non-human aesthetics and ethics.